Aging of Pelvic Floor in Animal Models: A Sistematic Review of Literature on the Role of the Extracellular Matrix in the Development of Pelvic Floor Prolapse - Gardella, Barbara; Scatigno, Annachiara Licia; Belli, Giacomo; Gritti, Andrea; Visoná, Silvia Damiana; Dominoni, Mattia (Frontiers in Medicine, 2022)
Pelvic organ prolapse (POP) affects many women and contributes significantly to a decrease in their quality of life causing urinary and/or fecal incontinence, sexual dysfunction and dyspareunia. To better understand POP pathophysiology, prevention and treatment, many researchers resorted to evaluating animal models. Regarding this example and because POP affects principally older women, our aim was to provide an overview of literature on the possible biomechanical changes that occur in the vaginas of animal models and their supportive structures as a consequence of aging. Papers published online from 2000 until May 2021 were considered and particular attention was given to articles reporting the effects of aging on the microscopic structure of the vagina and pelvic ligaments in animal models. Most research has been conducted on rodents because their vagina structure is well characterized and similar to those of humans; furthermore, they are cost effective. The main findings concern protein structures of the connective tissue, known as elastin and collagen. We have noticed a significant discordance regarding the quantitative changes in elastin and collagen related to aging, especially because it is difficult to detect them in animal specimens. However, it seems to be clear that aging affects the qualitative properties of elastin and collagen leading to aberrant forms which may affect the elasticity and the resilience of tissues leading to pelvic floor disease. The analysis of histological changes of pelvic floor tissues related to aging underlines how these topics appear to be not fully understood so far and that more research is necessary.